THE EFFECT OF BI RATE AND THE RUPIAH EXCHANGE RATE ON MUDHARABAH DEPOSITS IN SHARIA BANKING IN INDONESIA - Isra Hayati; Riska Amelia (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the effect of the rupiah exchange rate and the BI Rate on mudharabah deposits in Islamic banking in Indonesia. The period used in this study is 5 years, starting from 2016 to 2020. The population used is Islamic banking statistical data in Indonesia in monthly taken in 12 months for 5 years from 2016 to 2020. The sample used The data used is the complete statistical data of Islamic banking in Indonesia from the period 2016 to 2020. Based on the results of data analysis, partially the tcount value of the rupiah exchange rate is 7,443 the ttable value of 2,002 so that the rupiah exchange rate has a significant positive effect on mudharabah deposits. The tcount value of the BI Rate is -3.251 the ttable value of 2.002 so that the BI Rate has no significant effect on mudharabah deposits. Based on the Anova test, it is known that the F statistic value is 33,673 with a significance of 0.000. The R-Square value is 0.542, this means that the ability of the independent variable in explaining the variation of the dependent variable is 54.2%, while the remaining 45.8% is explained by other variables.Keywords: Rupiah Exchange Rate, BI Rate, Mudharabah Deposits